Blind landing - Paulsson, Bjp2(Brn Konow.s (New York : Harcourt Brace Jovanovich, 1972)
A young Norwegian Air Force pilot develops a deep friendship, increa ses in flying proficiency, and wins a championship in national competit ion.
Keywords: Flight training -- Fiction; Friendship -- Fiction